Combined multi-omics and physiological approaches to elucidate drought-response mechanisms of durum wheat - Arriagada, Osvin; Meneses, Claudio; Pedreschi, Romina; Núñez-Lillo, Gerardo; Maureira, Carlos; Reveco, Samantha; Villarroel, Valentina; Steinfort, Úrsula; Albornoz, Francisco; Cabas-Lühmann, Patricia; Silva, Manuela; Matus, Iván; et al. (Frontiers in Plant Science, 2025)
IntroductionDurum wheat is the most important cereal in the Mediterranean regions, where drought negatively affects grain yield. Therefore, our objective was to perform a multi-omics and integration analysis in conjunction with physiological trials to improve our understanding of drought tolerance mechanisms of durum wheat.MethodsGenome-wide association study (GWAS) for yield components was performed on a panel of 225 elite durum wheat genotypes evaluated in eight sites under irrigated and rainfed conditions. Based on physiological parameters (net photosynthesis, intracellular CO2 content, transpiration and stomatal conductance) and grain yield, contrasting genotypes (susceptible and tolerant) to drought were identified. A transcriptomic (RNA-seq), metabolomic and integration analyses were performed to identify genes and metabolites associated with tolerance in durum wheat.ResultsNine marker-trait associations were detected across 8 environments, and they were grouped into three QTL clusters (QTL_2A_TGW/GPS.1, QTL_2A_TGW/GPS.2, and QTL_2B_TGW/GPS.1), explaining between 5.15% and 14.29% of the phenotypic variation. One drought tolerant (QUC 3678-2016) and one susceptible (BRESCIA) genotype were identified based on physiological parameters. RNA-seq analysis showed that the genes regulated were mainly enriched in processes such as response to salicylic acid, plant organ senescence, synthesis of secondary metabolites, and immune response. Metabolic analysis showed that drought increased the contents of amino acids, sugars, and organic acids. The integration analysis identified 30 genes and six metabolites in the root and 30 genes and 10 metabolites in leaves as the primary variables in the drought-tolerant genotype, in which L-Proline was an important metabolite that allowed differentiating those two contrasting genotypes. A WRKY transcription factor was also positioned on the stable QTL QTN_2A_TGW/GPS.1 associated with the GENE-1342_238 SNP marker.DiscussionThese results open an opportunity to use new biomarkers in durum wheat breeding programs to develop resilient and high-yielding cultivars and ensure food security under water deficit conditions.